2023
DOI: 10.2147/cia.s369574
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults and Immune Thrombocytopenia: Considerations for the Clinician

Abstract: Many epidemiological studies have shown that the incidence of immune thrombocytopenia (ITP) increases after age 60 years and peaks in patients over age 80 years. Therefore, ITP is a concern for physicians taking care of older patients, especially regarding its diagnosis and management. The diagnostic work-up should exclude other causes of thrombocytopenia and secondary ITP, including myelodysplastic syndrome and drug-induced ITP. The treatment decision is influenced by an increased risk of bleeding, infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 143 publications
0
4
0
1
Order By: Relevance
“…Elderly individuals often encounter significantly higher perioperative risks linked to splenectomy compared to younger patients 58 . This population group are often deemed unsuitable candidates for splenectomy, especially if there is a pre‐existing increased risk of thrombosis or multiple comorbidities, resulting in their management with drug therapy for an extended period 59–61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly individuals often encounter significantly higher perioperative risks linked to splenectomy compared to younger patients 58 . This population group are often deemed unsuitable candidates for splenectomy, especially if there is a pre‐existing increased risk of thrombosis or multiple comorbidities, resulting in their management with drug therapy for an extended period 59–61 …”
Section: Discussionmentioning
confidence: 99%
“…58 This population group are often deemed unsuitable candidates for splenectomy, especially if there is a pre-existing increased risk of thrombosis or multiple comorbidities, resulting in their management with drug therapy for an extended period. [59][60][61] Although post-embolization syndrome is the most common minor complication, typically managed with conservative therapy, 62 major complications such as splenic abscess and splenic rupture may necessitate surgical or other interventional measures. 63 Our review of AEs following SE revealed an incidence of 1.3% of severe AEs requiring intervention.…”
Section: Study Year (Reference)mentioning
confidence: 99%
“…43 However, contradictory data have shown no clear decrease in the effectiveness of splenectomy in older people. 44 Therefore, splenectomy should not reasonably be contraindicated in older patients; the existence of comorbidity and the degree of frailty of the patient should lead more to the rejection of surgery than age alone. In patients with severe comorbidities for whom splenectomy is contraindicated, it has been suggested that partial splenic embolization could be a safe and alternative therapy and generates a long-term durable response.…”
Section: Clinical Criteriamentioning
confidence: 99%
“…Some have suggested that the response to splenectomy is poor in patients over 60 years old and with many complications but still with 56% prolonged response 43 . However, contradictory data have shown no clear decrease in the effectiveness of splenectomy in older people 44 . Therefore, splenectomy should not reasonably be contraindicated in older patients; the existence of comorbidity and the degree of frailty of the patient should lead more to the rejection of surgery than age alone.…”
Section: Are There Predictors Of the Response To Splenectomy?mentioning
confidence: 99%
“…Después de una búsqueda cuidadosa, existen otras intervenciones que podrían ser útiles, como el uso de agentes biológicos (por ejemplo, Rituximab) y la terapia combinada 10 . Las guías no son claras sobre cómo proceder después de la terapia de segunda línea ni cuando se considera una TIP refractaria 11 ; se han probado múltiples esquemas de combinación con un rango variable de éxito: por ejemplo, el uso de ciclofosfamida, acompañado de prednisona, vincristina, rituximab y otros medicamentos, han demostrado respuestas hasta del 60 % 12,13 . Además, el historial médico, así como los hallazgos físicos y de laboratorio específicos deben evaluarse cuidadosamente, sobre todo cuando los pacientes tienen sospecha de enfermedades infecciosas concurrentes.…”
Section: Introductionunclassified